Review: Closed-Cell Metallic Foams Produced via Powder Metallurgy - Nathan Behymer; K. Morsi (Metals, 2023)
The production of closed-cell metallic foams has been of interest to the scientific community and industry for decades, owing to their unique properties, which include high specific strength and stiffness, buoyancy, shock absorption, and crash worthiness. One of the approaches for their fabrication relies solely on the use of powders and is manifested in what has been referred to as the powder metallurgy (PM) route. This review discusses the underlying fundamentals of the process, and recent developments together with our current understanding. The effect of process parameters on the developed foam structure is reviewed for a range of metals, alloys, and metal matrix composites. Fundamental foaming mechanisms and characteristics are discussed.